Effects of accounting and corporate governance reforms on income smoothing practices by Indonesia listed firms - Trisanti, Theresia (2012)
Recent accounting research reveals that income smoothing (IS) practices in developing and emerging economies are higher than in developed-country. As an emerging market, Indonesia has a high occurrence of IS practices since around 65% of Indonesian listed firms have committed to it (Damayanthi, 2002; Prasetyo & Astuti, 2002). Motivated by these facts, this study seeks an empirical investigation on the effectiveness of the accounting and corporate governance (CG) reforms from the perspective of IS practices in Indonesia. Accordingly, four research objectives have been established. First is to investigate the effect of CG and accounting standard reforms on IS practices by Indonesian listed firms in the period from 1995 to 2009. Second is to verify the effect of two IS instruments: discretionary accounting changes (DAC) and non-recurring items to the IS practices. Third is to study the effects of selected Indonesian listed company CG attributes to the IS practices and fourth is to investigate the effect of company’s specific characteristic attributes on the IS practices. The IS practice was measured with two models: the coefficient variation of sales to income index by Eckel (1981) and the smoothing behavior index by Moses (1987). A review of the Indonesian CG Codes revealed that there were two attributes that was expected to have impact on IS practices, the independent boards and the independent audit committee. Six company’s specific characteristic attributes were also used to assess their impact to IS practices, institutional ownerships, company size, type of industry, debt financing, external auditor quality,and profitability. The research sample was drawn from the DataStream and Indonesian Capital Market Directory (ICMD) database for the years of 1995 to 2009 and divided into three different periods. The first period was during the financial crisis (1995- 1999), the second was when the various corporate governance initiatives took place (2000-2004), and the third was when Indonesian general accounting principles converged to IFRS (2005-2009). For the first research objective, the study concluded there was a significant difference of IS practices before and after the introduction CG codes and IFRS respectively. For the second research objective, the study found that Indonesian listed firms tend to use DAC and nonrecurring items to smooth their income figures. For the third and fourth research objectives, the findings did not support the proposition that a higher proportion of independent directors and independent audit committee would provide more effective monitoring mechanism in constraining IS practices. Type of industry was also negatively associated with the IS practices for three different periods. Meanwhile, institutional ownership and company size had also no significant relationship to IS practices during financial crisis period (1995-1999), but they were after the introduction of CG codes (2000-2004) and after the convergence to IFRS (2005-2009). For debt financing, profitability and external audit quality there were significant relationship to IS practices for all three different period. Overall, the study concludes that IS practices decreased significantly among Indonesian listed firms after the introduction of CG Codes and IFRS but its percentage was still high. This suggests that although Public Interest Theory (PIT) lays foundation to government to introduce CG and IFRS but from Positive Accounting Theory (PAT) perspective, such initiative will constraint management to choose standards on accounting and governance that may contradict to maximize their benefits. Therefore, using Agency Theory perspective, the introduction of CG and accounting reforms should be equipped with a new model and framework to better manage the relationship among agents and principals that involve government, stakeholders and companies through some policies and regulations.